Stem-Cutting Propagation of Adlay (Coix lacryma-jobi L.): Effects of Genotype and Stalk Portion on Vegetative Growth - Jay Ryan Soliva Galve; Melvin John Abulag Nalasa; James Victor Rana Aradilla (Agro Bali : Agricultural Journal, 2026)
Adlay production is constrained by its long seed-propagation maturity period, underscoring the need for alternative propagation methods. This study evaluated the effects of genotype and stem-cutting position on vegetative propagation of adlay. The experiment was conducted from November 2023 to January 2024 under screenhouse conditions at the BISU Bilar Campus, using a 2 × 3 factorial design with three replications in a completely randomized design. Two adlay genotypes (Gulian and Kiboa) and three stalk portions (basal, middle, and upper) were evaluated. Kiboa showed greater sprouting (1.78) and tillering performance (3.00) than Gulian. Stalk portion influenced all vegetative traits measured (p < 0.001). Basal cuttings exhibited the highest sprouting percentage (35%) and number of sprouts (4.00), while middle cuttings produced taller plants (155.34 cm) with more leaves (10.00), nodes (6.00), and tillers (5.00). These findings confirm that stem cuttings, particularly from the basal and middle portions, offer a practical and efficient method for rapid, uniform adlay propagation, supporting breeding programs, germplasm conservation, and improved availability of planting material for farmers.